Measurement of cement’s particle size distribution by the buoyancy weighing-bar method - Rondang Tambun Tambun; Nofriko Pratama; . Ely; Farida Hanum (Syiah Kuala University, 2015)
One of the important characteristics of cement quality is particle size distribution. There are several simple methods to measure the particle size distribution of cement based on the Stokes diameter, like Andreasen pipette method, sedimentation balance method, centrifugal sedimentation method, etc. A major disadvantages of these methods are they are time consuming process and require special skills. Particle size distribution also can be analyzed by using a different principle through microscopy, laser diffraction/scattering methods and Coulter counter method. Even these methods produce highly accurate results within a shorter time, however, the equipments are expensive. In the present study, it has developed a new method to overcome the problem. The method is the buoyancy weighing-bar method. This method is a simple and cost-effective. The principle of the buoyancy weighing-bar method that the density change in a suspension due to particle migration is measured by weighing buoyancy against a weighing– bar hung in the suspension, and the particle size distribution is calculated using the length of the weighing-bar and the time–course change in the the apparent mass of the weighing–bar. This apparatus consists of an analytical balance with a hook for underfloor weighing, and a weighing–bar, which is used to detect the density change in suspension. The result obtained show that the buoyancy weighing–bar method is suitable for measuring the particle size distribution of cement, and the result is comparable to that of determined by settling balance method.